Population Ecology, Reproductive Behaviour And Feeding Habit Of Helopeltis Antonii Signoret On Cashew (Anacardium Occidentale L.) Plants - Siswanto (2007)
Helopeltis antonii Signoret (Hemiptera: Miridae) is well known as one of the important pest of the cashew plant, Anacardium occidentale L. Both the nymph and adult stages feed on young and succulent parts of the plant such as the young leaves, shoots, inflorescences and fruits causing death of those parts. This research was conducted with the objectives to establish age-specific life table, to investigate some biological aspects of H. antonii, to study the effect of damage caused by H. antonii on shoot, inflorescence and fruit, and also to study some ecological aspects related to H. antonii population in the field. The studies were conducted in pesticide-free cashew plantation belonging to smallholders and also in the laboratory of Estate Service of Wonogiri Regency in Ngadirojo district, Wonogiri, Central Java, Indonesia from March 2004 to May 2006. The life table of H. antonii revealed a high hatchability but a bulk mortality occurred at early nymphal stages and relatively fewer death during the adult stage. The contribution of the female towards female births (mx) was at its maximum on the 16th day of oviposition.The population parameters of H. antonii fed cashew showed that the intrinsic rate of natural increase (rm) was 0.092/female/day, the net reproductive rate (Ro) was 12.84, the capacity for increase (rc) was 0.090, the finate rate for increase ( λ ) was 1.097 female/day, and mean generation time (T) was 27.70 days with the population doubling (DT) every 7.52 days. Biological studies revealed that H. antonii feeding lesions developed faster on inflorescence and shoot compared to fruits. The lesions on shoot and inflorescence produced depressed and wrinkled surface which then dried up within four days. Meanwhile it caused depression on apple and flattened the surface on nut. Feeding preference with no choice experiment suggested that H. antonii preferred to feed on shoot and young fruits rather than the inflorescence and older fruits. Results in the choice experiment suggested that H. antonii preferred to feed on shoot compared to inflorescence and fruits. The female preferred to oviposit on inflorescence compared to shoot and fruit. The premating period for both male and female H. antonii was one day. Sex ratio of females to males did not influence the number of eggs laid. However, overcrowded males seemed to influence female longevity. The frequency of matings did not influence the number of eggs laid and the hatchability, eventhough, females which mated more than once tended to lay more eggs. Damage assessment study revealed that the percentage of shoot, inflorescence and fruit death increased with the number of lesions. Apart from the number of lesions, position of lesions and stage (age of part attacked) also affected damage intensity, particularly on inflorescence and fruits. Small or young fruits were not able to tolerate heavy damage by H. antonii, whereas older fruits were relatively not affected by the damage. Field experiments indicated that cashew fruit particularly small and medium sized were more susceptible to H. antonii feeding lesions compared to inflorescences. The infestation of H. antonii was linked to the phenology of the cashew plants. Higher percentage of inflorescence death occurred in the second phase of flowering season, meanwhile higher percentage of fruit death occurred in the third flowering season. Studies on the population fluctuation and dispersion of H. antonii in cashew plantation indicated that the fluctuation in the population of H. antonii was cyclical with the population peaking around July when cashew shoots and inflorescences were abundant. The population began to increase just after the rainfall season stopped and reached the peak three months later when rainfall was intermittent low. Number of shoots and inflorescences of cashew plants had significant influence on the number of H. antonii. The trend of population abundance was not directly associated with the rainfall, but rainfall influenced the physiology of the cashew plant to produced flushes/shoots and inflorescences. Distribution analysis using various indices of dispersion and regression models indicated an aggregated distribution when the population was high during flushing-flowering season of cashew plants and a regular or random distribution when the population was low during post-flowering season.